No hay lugar lejano - Ibaven, Michel (Mexico, 2012)
The Rarámuri community has lived in the Sierra Tarahumara ever since they can remember. Now they are facing banishment due to the touristic potential of the area.
Duration: 01:22:00
Keywords: Documentary films